2015
DOI: 10.1007/s00167-015-3517-8
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic anatomical, histological and magnetic resonance imaging correlation of the lateral capsule of the knee

Abstract: In fresh-frozen cadaveric specimens, macroscopic and MRI evaluation of the lateral capsule of the knee revealed variations in morphology without consistent capsuloligamentous anatomy and specifically no discrete lateral capsular ligament. Further investigation in the form of clinical and mechanical relevance of the lateral capsular structures is of paramount importance before limited anatomical data can be utilized to drive clinical decision-making and patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 24 publications
1
49
0
2
Order By: Relevance
“…These findings suggest that a proposed ligamentous structure in the anterolateral capsule does not have tensile properties like ligaments. This is in accordance with a histological study, which compared the anterolateral capsule to the ACL . The collagen pattern of the thickenings in the anterolateral capsule were organized into individual bundles, indicating that the anterolateral capsule includes a combination of multiple thickenings and not a homogenous entity such as the ACL.…”
Section: Discussionsupporting
confidence: 89%
“…These findings suggest that a proposed ligamentous structure in the anterolateral capsule does not have tensile properties like ligaments. This is in accordance with a histological study, which compared the anterolateral capsule to the ACL . The collagen pattern of the thickenings in the anterolateral capsule were organized into individual bundles, indicating that the anterolateral capsule includes a combination of multiple thickenings and not a homogenous entity such as the ACL.…”
Section: Discussionsupporting
confidence: 89%
“…47,19,31,37 Moreover, it is possible that the mid-third capsular thickening located at the confluence of capsular layers is more noticeable in some individuals than others, further contributing to the widely ranging prevalence of reported ALL and/or mid-third capsular ligament in published literature. 48,13,19,31,37,45,47 …”
Section: Discussionmentioning
confidence: 99%
“…Three different patterns have been reported in relation to the landmark represented by the FCL: (1) The ALL is always anterior and distal to the FCL (Vincent et al, ; Claes et al, ; Helito et al, ; Dombrowski et al, ; Stijak et al, ); (2) The ALL is always proximal and posterior to the FCL (Dodds et al, ; Cavaignac et al, ); or (3) The ALL and the FCL share a common attachment (Kosy and Mandalia, ; Runer et al, ). Another group of authors observed a variant set of three patterns (Kosy and Mandalia, ; Caterine et al, ; Daggett et al, ; Rezansoff et al, ; Helito et al, 2016a, 2016b; Runer et al, ; Kosy et al, ; Macchi et al, ; Shea et al, ; Watanabe et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…, 2014Helito et al, 2013;Dodds et al, 2014;Bonasia et al, 2015;Caterine et al, 2015;Daggett et al, 2015;Guenther et al, 2015;Kosy and Mandalia, 2015;Pomajzl et al, 2015;Roessler et al, 2015;Taneja et al, 2015;Van der Watt et al, 2015;Cavaignac et al, 2016;Helito et al, 2016aHelito et al, , 2016bMacchi et al, 2016;Musahl et al, 2016;Parker and Smith, 2016;Runer et al, 2016, Stijak et al, 2016Roessler et al, 2017), but there are controversies regarding the attachment in relation to the FCL and the popliteus muscle tendon. Three different patterns have been reported in relation to the landmark represented by the FCL: (1) The ALL is always anterior and distal to the FCL (Vincent et al, 2012;Claes et al, 2013;Helito et al, 2013Helito et al, , 2014Dombrowski et al, 2016;Stijak et al, 2016);…”
Section: Does the Femoral Attachment Have A Constant Relationship Tomentioning
confidence: 99%